Superhydrophilic polyethersulfone-based electrospun nanofibrous ultrafiltration membranes for oily wastewater treatment - Issa Al-Husaini, Issa Sulaiman (2020)
Lately, oil polluted water and its separation have received much attention in the context of growing environmental concerns in broad. In this regard, technology based on polymeric electrospun nanofibrous membranes (ENMs) has become an emerging solution for oil effluents, water filtrations and water treatments. However, highly porous structure and inadequate mechanical integrity of ENMs could result in great fouling tendency towards rapid flux deterioration in oil-water separation, unless inhibited. Thus, in this work, some novel ultrafiltration (UF) ENMs incorporated with iron oxide (Fe3O4) and hydrous manganese dioxide (HMO) nanoparticles (NPs) were synthesized. Subsequently, these UF-ENMs were characterized to determine their effectiveness for the removal o f oil from industrial wastewater. The mechanical property and hydrophilicity of polyethersulfone (PES)-based ENMs were improved by three strategies. First, ^-methyl-pyrrolidinone (NMP) was added to dimethylformamide (DMF), wherein the solvent stimulated fusion of the inter-fiber junctions was enhanced. Second, Fe3O4-HMO NPs were inserted into the ENMs to improve their anti-fouling resistance against oil molecules. Third, hot press technique was used to strengthen the electrospun mat. The morphology, structure, mechanical strength, water contact angle (WCA), water permeability and oil emulsion in water filtration capacity of these prepared ENMs were evaluated. The results disclosed an enhancement in the mechanical strength, hydrophilicity, permeability and selectivity of these ENMs due to the inclusion of Fe3O4-HMO NPs. Compared to pristine ENMs, the tensile strength and the elongation-at-break of the Fe3O4-HMO NPs incorporated ENMs were correspondingly improved by 225.88% and 40.91%, whereas the WCA was reduced by 89.8% (from 123.27° ± 0.23 to 12.34° ± 0.19). It was also found that the hot pressed PE/Fe3O4-HMO ENMs possessed smaller pore diameter (61.05 nm) compared to pristine PES ENMs (97.15 nm). The Fe3O4-HMO NPs modified ENMs were found to exhibit excellent oil elimination (98.37% ± 0.49 and 91.02% ± 0.69) and outstanding water flux recovery performance (87.32% ± 0.70 and 74.65% ± 0.73) when tested with synthetic oil solution (12,000 ppm) and oily effluents (7,000 ppm), respectively. Water productivity o f over 4,000 L/m2h was achieved without forfeiting the rate o f oil removal under gravity. The observed improved low flux declination revealed by the proposed ENMs was attributed to their improved surface resistance mediated oil anti-fouling qualities. The enhanced mechanical and oil anti-fouling traits of the prepared UF-ENMs were established to be a prospective for the treatment o f diverse industrial oily effluents, especially emulsions of oil-water.